# Calculus

posted by .

Derivative

Differentiate

f(x)=(5x-4)^2

There are two ways to do this:
(1) let u = 5x-4, and use the "chain rule", df/dx = df/du * du/dx
OR
(2) expand the polynomial to
f(x) = 25 x^2 -40x + 16
and differentialte it term-by-term.
You will get the same answer either way.

Let's use the first way, because it is something you may need for other problems
u = 5x-4
du/dx = 5
f(u) = u^2
df/dx = df/du * du/dx
= 2 u * 5 = 10(5x -4) = 50x - 40

## Similar Questions

1. ### Differentiation

How do you find f'(x), f''(x) of f(x) =ln (1-x) IF f(x) = ln (1-x) Then use the chain rule with u(x) = 1-x f(u) = ln u df/dx = df/du du/dx f'(x) = -1/(1-x) Use the chain rule again: f"(x) = -[-1/(1-x)^2]*(-1) = -1/(1-x)^2 What is the …
2. ### calculus

I am having trouble with this problem also derivative differentiate f(x)=(3-x)^4(x+5)^3 so far I have 4(3-x(x+5)^3+3(x+5)(3-x) Not quite right. Treat it as d/dx[u(x) + v(x)] = u dv/dx + v du/dx u(x) = (3-x)^4 v(x) = (x+5)^3 du/dx = …
3. ### Math, Calculus

Find the derivative of the function. y= xcosx - sinx What's the derivative?
4. ### Calculus

Can anyone explain how to use the chain rule and power rule together to find the first derivative and please do these examples. f(x) = -3x^4/(sqrt(4x-8)) g(x) = ((2x+5)/(6-x^2)^4 g(x) = (8x^3)(4x^2+2x-3)^5 y = [1/(4x+x^2)^3]^3 Thank …
5. ### Calculus

How do I use the chain rule to find the derivative of square root(1-x^2) also, are there any general hints or tips for determining when the chain rule and product or quotient rule should be used?
6. ### calculus

I have been asked to solve this two different ways. The first way is to use the chain rule and then simplify (which I have already done properly), and the second way is to simplify and then differentiate (not necessarily with the chain …
7. ### calculus

Please help. Applying the chain rule, how do I find the derivative of f(x)=In(e^x-e^-x) (x>0) and then using this answer use the quotient rule to find the second derivative. I cannot do this so any answer greatly appreciated.
8. ### Calculus

I'm having problems with this one. Can't get the right answer. Differentiate the following using the chain rule. f(x) = squareroot(x^2+1)/(3x+1) I know that I can take the whole thing and put it to the (1/2) and differentiate that …
9. ### Calculus

What would an example of a logarithmic function that contains two trig functions within it where you would need to use chain rule and product rule to take derivative look like?